Performance-based Financing in Africa: Time to Test Measures for Equity. (July 2018) - Ridde, Valéry; Gautier, Lara; Turcotte-Tremblay, Anne-Marie; Sieleunou, Isidore; Paul, Elisabeth
Over the past 15 years, hundreds of millions of dollars have been invested in reforms founded on performance-based financing (PBF) in low- and middle-income countries. While evidence on its effectiveness and efficiency is still controversial, there appears to be an emerging consensus that equity has not been adequately considered. In this article, we show how PBF-type interventions in Africa have not sufficiently taken into account equity of access to care for the worst-off and their financial protection. In reviewing the history of health reforms in Africa, we show that this omission is nothing new. We suggest that strategic purchasing and PBF-type actions would benefit from being implemented in ways that promote equity and the financial protection of populations in Africa. Without such a reorientation of reforms, it will be impossible to achieve universal health coverage by 2030.